Understanding consumer mindset helps Singapore’s policymakers to introduce new sustainability policies that shape Singapore’s culture towards a single-use plastics free economy - Teo, En Guo (2025)
The plastics have become one of the most important, necessary, valuable and commonly used materials for consumers daily lives in the global economy (Science History Institute, 2024; Rhein and Schmid, 2020; Nguyen et al., 2022). Currently, the global plastic consumption is over 400,000,000 tonnes, and the future global plastic consumption is projected to reach over 1,200,000,000 tonnes in 2060 if there are no new policies to reduce the global plastic consumption (Braun, 2023). As of 2023, it was projected that there will be 389,300,000 tonnes of plastic waste generated in worldwide (Alves, 2023). In 2060, it is projected that there will be 1,014,100,000 tonnes of plastic waste generated in worldwide (Alves, 2023). In 2060, it is projected that landfill will be the main disposal method and recycling rate will be less than 20% in worldwide (Alves, 2023).